Improvement of the Measuring Accuracy of the Raman Lidar for Remote Detection of the Hydrogen Gas - Choi, In-Young; Baik, Sung-Hoon; Park, Nak-Gyu; Kang, Hee-Young; Kim, Jin-Ho (International journal of precision engineering and manufacturing, 2018)
Hydrogen gas detection technique is very important because it is very flammable and explosive. A Raman lidar system is one of the techniques for the detection of hydrogen gas remotely. The signal to noise ratio of the Raman lidar is not high, because Raman scattering signals by the hydrogen gas are very weak and its signals include the background noise signals such as the pumping laser, laser-induced fluorescents signals, and ambient light. This paper discusses the improvement of the accuracy of the Raman lidar system for measuring hydrogen gas by eliminating the background noise signals. To verify the accuracy improvement effects, experiments of measuring the hydrogen gas concentration are carried out. As the results of the experiment, The coefficient of the determination(R 2 ) of the calibrated Raman signal of the hydrogen gas distribution by using the background noise signals was improved from 0.9985 to 0.9995 and the mean of the measuring error rates are decreased from 0.9794 to 0.7179, which is an improvement of about 27%.